Manorial and grange complexes as a cultural heritage of the agricultural landscape in the management of commune space: A case study of Tarnowo Podgórne, Wielkopolska - Wilkaniec, Agnieszka; Szczepańska, Magdalena (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2017)
Manorial and grange complexes are characteristic elements of the rural cultural landscape; they constitute significant evidence of the farming tradition of a region. Unfortunately, nowadays these complexes have often become dilapidated, their legibility has been obliterated and there have been radical changes in the spatial context. The aim of this study was to determine whether manorial and grange complexes were given proper attention in the development and strategic plans worked out by communes. The commune of Tarnowo Podgórne, stretching along the western boundary of Poznań city, was selected as a case study and research area. An attempt is also made to recognise what protective provisions the local law makes for those complexes. The authors think that the quality of plans concerning the facilities under study is unsatisfactory. The Land Use Plan includes recommendations to protect nonexistent facilities and lists a complex located beyond the commune boundaries. Although the Plan emphasises the significance of manorial and grange complexes, there are no local spatial development plans for most of them. Some plans referring to the spatial structures under analysis are imprecise and incomplete, which results in ineffective protection.
Keywords: land use plan; local spatial development plans; manorial and grange complexes; rural landscape; spatial management; Tarnowo Podgórne; Wielkopolska